A solvent free method to characterize the effect of recycled asphalt shingles on virgin asphalt binder. (20th January 2019) - Yan, Yu; Hernando, David; Roque, Reynaldo
Abstract: The current design guideline of asphalt mixtures containing recycled asphalt shingles requires accurate characterization of shingle binder and its effect on virgin binder. This characterization employs hazardous solvents to extract and recover the shingle binder prior to testing. The objective of this study was to determine whether an enhanced mortar characterization method, which eliminates the need for chemical solvents by testing mortars composed of virgin binder and fine shingle fraction, can be used to predict the rheological properties of shingle binder blends with virgin binder. Superpave binder tests (dynamic shear rheometer and bending beam rheometer) were performed on six mortars combinations of two shingle sources and three virgin binders. The change in true grade of virgin binders caused by shingle binder was quantified by using a parameter named grade change rate (°C/%shingle binder). True grades of shingle binder blends predicted by grade change rate were compared to values measured on manually-prepared binder blends at multiple binder replacement rates of 15%, 30% and 100%. High and low temperature grades measured on blended binders were successfully predicted by the enhanced mortar approach. Moreover, the critical low-temperature parameter (delta Tc), which has been used to describe the embrittlement introduced by shingle binder, was also accurately predicted by using the stiffness-based and relaxation-based grade change rate. In conclusion, the enhanced mortar approach not only provides accurate estimates of the rheological properties of binder blends, but also eliminates the exposure to hazardous solvents currently employed during the extraction and recovery of the recycled binder. Highlights: Extracted shingle binder cannot be characterized by standard binder test equipment. Enhanced mortar approach eliminates the use of solvent-based extraction and recovery. Grade change rate predicts low and high temperature grades of shingle binder blends. Shingle binder reduces relaxation more than it increases stiffness of virgin binder. Predicted ΔTc of shingle binder blends agreed with values from measured properties.